Using Markov chains to forecast the exports of Iraqi crude oil - صادق, نازك جعفر; جميل, سعد عبيد (Journal of Economics and Administrative Sciences, 2019)
In this paper, the topic of forecasting the changes in the value of Iraqi crude oil exports for the period from 2019 to 2025, using the Markov transitional series based on the data of the time series for the period from January 2011 to November 2018, is real data obtained from the published data of the Central Agency Of the Iraqi statistics and the Iraqi Ministry of Oil that the results reached indicate stability in the value of crude oil exports according to the data analyzed and listed in the annex to the research.Keywords: Using Markov chains